Green giants how smart companies turn sustainability into billion-dollar businesses - Williams, E. Freya (AMACOM - American Management Association, 2015)
This book examines nine companies that are merging social responsibility with wild profitability - and reveals the six factors responsible for their success, including: iconoclastic leadership fueled by deep conviction and a rebellious streak; disruptive innovation that uses sustainability to spur the development of radically better products and services; a higher purpose that ignites the company - when the mission leads, profits follow. This new breed of billion-dollar businesses proves it's possible to achieve enormous success while implementing sustainable principles that help consumers live better lives. Packed with eye-opening research, exclusive interviews, and enlightening examples from Chipotle, Toyota, Unilever, Tesla, General Electric, and more, this book serves as a blueprint for sustainable success that anyone can follow. --
Includes bibliographical references and index. - Print version record
Keywords: Leadership; Social responsibility of business; Industrial management -- Environmental aspects; Success in business; Entreprises; Responsabilité sociale; Gestion d'entreprise; Aspect de l'environnement; Succès dans les affaires; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Industrial management; Environmental aspects